2016
DOI: 10.1007/s00167-016-4297-5
|View full text |Cite|
|
Sign up to set email alerts
|

The role of bone void fillers in medial opening wedge high tibial osteotomy: a systematic review

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 46 publications
6
75
0
1
Order By: Relevance
“…This is in accordance with epidemiological studies that show more people with knee OA in women than men who are done elsewhere such as in the United States and Egypt. This may be related to the hypothesis that the number of people with OA is due to hormonal factors, namely reduced estrogen levels and progestin at the age of menopause (Slevin, 2016;Sun, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with epidemiological studies that show more people with knee OA in women than men who are done elsewhere such as in the United States and Egypt. This may be related to the hypothesis that the number of people with OA is due to hormonal factors, namely reduced estrogen levels and progestin at the age of menopause (Slevin, 2016;Sun, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the authors concluded that synthetic bone substitutes cannot be recommended. 11 In a prospective study by Ferner et al, 12 significantly higher rates of nonunion were observed after augmentation without synthetic bone grafting. Problem solved, and the evidence seemed clear: there is no need for bone grafting in open-wedge HTOs.…”
Section: See Related Article On Page 2621mentioning
confidence: 94%
“…The work by Nha et al 16 seems to support previous studies. [9][10][11] Nonetheless, based on the current published evidence, we can possibly conclude that bone grafting, whether with autologous or synthetic bone graft, is not needed for open-wedge HTOs with gaps <10 to 12 mm. Finally, this topic offers itself for a high-quality randomized prospective multicenter study.…”
Section: See Related Article On Page 2621mentioning
confidence: 97%
“…Two recent systematic analyses compared historically reported groups of patients with autograft, allograft, synthetic material, and no bone graft, demonstrating comparable rates of nonunion or delayed union. 27,28 One recommendation was that in corrections <10 mm and with the use of locking-plate technology, bone graft may not be necessary. 28 However, the primary limitation with locking plates tends to be implant-related discomfort, which has been reported in a large proportion of patients, approaching approximately 40% in some series.…”
Section: Implant Optionsmentioning
confidence: 99%
“…27,28 One recommendation was that in corrections <10 mm and with the use of locking-plate technology, bone graft may not be necessary. 28 However, the primary limitation with locking plates tends to be implant-related discomfort, which has been reported in a large proportion of patients, approaching approximately 40% in some series. 26 In recent years, alternative fixation devices have been designed using polyetheretherketone (PEEK).…”
Section: Implant Optionsmentioning
confidence: 99%